Natural Leaching of the Highly Salt Affected Soils of Western Rajasthan - Gupta, I.C.; Abichandani, C.T. (Journal of Soil and Water Conservation, 2022)
Salineg round waters of salinity level 4 to 10 mm nos EC/cm occur widely in Western Rajasthan Some of these of salinity 4 to 8 mmhos. EC/cn are generally used for growing salt tolerant Kharchi wheat. Crop is, however, generilly grown alternate year. Abichandani & Bhatt (1965) report that two rainy seasons of 250.400 mm ranifall serve to reclaim the soil and that no crop is taken during the intervening rainy seasons as the salts accumaulate in the upper few centi-meters of the soil, because of capillary rise during the following hot season after the saline water irrigation is over. Kelley (1953) in his review summarised that leaching is vitally important whenever irrigation is practised and adequate moderate salinity of irrigation water may be advantageous provided its calcium is not unduly low. He alsostated that natural precipitation may leach out salts that accumulate as a result of applying saline irrigation water and that if the amount of precipitation is deficient to penetrate the soil to depth below the root zone, the accumulation of salts may largely be prevented.